Industry Responsibilities in Tackling Direct‐to‐Consumer Marketing of Unproven Stem Cell Treatments. Issue 2 (10th July 2017) - Master, Z; Fu, W; Paciulli, D; Sipp, D
Abstract : The direct‐to‐consumer marketing of unproven stem cell interventions (SCIs) is a serious public health concern. Regulations and education have had modest impact, indicating that different actors must play a role to stop this unfettered market. We consider the role of the biotech industry in tackling unproven SCIs. Grounded in the concept of corporate social responsibility, we argue that biotech companies should screen consumers to ensure that products and services are being used appropriately and educate employees about unproven SCIs.